Differential polynomials generated by some complex linear differential equations with meromorpfic coefficients - Belaϊdi, Benharrat (Array, 2008)
Abstract: In this paper, we investigate the relationship between small functions and differential polynomials g(z) = d2f'' + d1f' + d0f, where d0(z), d1(z), d2(z) are meromorphic functions which are not all equal to zero with ρ(dj) < n (j = 0,1,2) generated by some second order linear differential equations with meromorphic coefficients